The Effect of Digital Media on Grammar Mastery for TOEFL Preparation - Jasrial, Dedi; Zaim, M; Yunita, Wisma (UNIB Press, 2024)
In this digital era, many scholars have reported the effectiveness of digital educational platforms in teaching English grammar. However, little research has utilized digital media, such as YouTube videos and the Quizizz platform, to teach TOEFL grammar. To fill this gap, this research aims to investigate the effect of and students’ perceptions of these two platform interventions on students’ grammar mastery for TOEFL. This experimental one-group pre-test-post-test design was applied to students of the Registration Certificate for Nutrition program at the Bengkulu Health Polytechnic of the Ministry of Health, consisting of 42 persons. The data of this research were the grammar tests given in the pre-test and post-test and the students’ perception questionnaire. A non-parametric Wilcoxon test using SPSS package version 16 and descriptive statistics were used to analyze the data. The result indicates that students’ grammar mastery for TOEFL preparation improved after giving interventions using YouTube and Quizizz platforms. Moreover, the results show students overwhelmingly perceive YouTube videos and Quizizz quizzes as highly effective for improving their grammar mastery for TOEFL preparation. They strongly believe their understanding of grammar improves and express high motivation, confidence, engagement, and effectiveness in applying and remembering grammar concepts. In brief, this result emphasizes the efficacy of utilizing multimedia resources and interactive platforms within educational settings, particularly in teaching English grammar. It is suggested instructors are encouraged to incorporate YouTube videos and Quizizz quizzes into TOEFL preparation courses to boost grammar mastery, leveraging multimedia resources for enhanced learning outcomes in the digital era.